Analysis of the predictive value of red cell distribution width (RDW) and hemoglobin-to-RDW ratio (HRR) on the prognosis of patients undergoing total laryngectomy - Fang, Zhixuan; Niu, Kai (Frontiers in Oncology, 2025)
BackgroundSystemic inflammatory markers, particularly pretreatment red cell distribution width (RDW) and hemoglobin to red cell distribution width ratio (HRR), have been associated with prognosis in several cancers. This study aimed to investigate the relationship between the preoperative RDW, HRR and clinicopathologic characteristics of patients undergoing total laryngectomy and their correlation with prognosis.MethodsThe optimal cut-off values of RDW and HRR to the overall survival (OS) of patients were determined by the receiver operating characteristic (ROC) curves, which in turn divided the patients into high-value and low-value groups for further stratified analyses. Patient survival was analyzed using Kaplan-Meier survival curves. Additionally, univariate and multivariate Cox regression analyses were conducted to evaluate the predictive roles of RDW and HRR on the prognosis of patients following total laryngectomy.ResultsThe high RDW group demonstrated statistically significant associations with TNM clinical stage, cervical lymph node metastasis, and vascular infiltration (P < 0.05). Similarly, the low HRR group exhibited significant associations with gender, histologic grade, TNM clinical stage, cervical lymph node metastasis, and vascular infiltration (P < 0.05).The optimal cut-off values for predicting overall survival (OS) for patients, as determined by ROC curves, were 13.75 for RDW and 10.79 for HRR. Additionally, RDW emerged as an independent prognostic factor for OS in this population (HR = 3.060, 95% CI 2.222–4.215, P < 0.001).ConclusionPreoperative RDW and HRR are prognostic risk factors for OS in patients undergoing total laryngectomy, with RDW serving as an independent predictor of prognosis.